The effect of organizational culture, personality, job satisfaction, and trust on school supervisor performance - Virgana Virgana; Soeparlan Kasyadi (Journal of Education and Learning (EduLearn), 2020)
This research was about school supervisors who play a strategic role in the management of human resources in the school environment. The study aims to determine the direct and indirect influences of organizational culture, personality, job satisfaction, and trust on the school supervisor's performance. The research samples were 180 supervisors of the school Education Office Special capital Jakarta. Data collection using questionnaires with a Likert scale, before analyzed the obtained data will be validated and reliably in respondents outside of the research sample. Data were analyzed through path analysis, as data analysis requirements were tests of normality, homogeneity, and linearity. Research results there was a direct influence of organizational culture, and personality on job satisfaction; Organizational culture, and personality on trust; Organizational culture, and personality on performance; Job satisfaction, and trust on performance, then there was an indirect influence of organizational culture through job satisfaction on the performance of school supervisor. The conclusion that the performance of the school supervisor at the Education Office of Jakarta was influenced by variations level of organizational culture, personality, and Trust, but the personality of school supervisors should have a priority attention to improving their performance.